Spontaneous hemoperitoneum in pregnancy: report of two cases - Pillai, Swapna Surendran; Hassinar, Abeer; Kutty, Sathiamma Puthuvilayil; Devi , Girija (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
The condition known as spontaneous hemoperitoneum in pregnancy (SHiP) is characterized by an accumulation of fluid in the abdominal cavity and a vague collection of symptoms. Specifically, intrauterine pregnancy increases the chance of death for both the mother and the fetus, making SHiP a potentially lethal illness when it coexists. Here, we discuss two cases of spontaneous hemoperitoneum in pregnancy that resulted from placenta accreta spectrum and endometriosis, and happened in the second and third trimesters, respectively.